An inverse Ruddlesden-Popper nitride Ca7(Li1−xFex)Te2N2 grown from Ca ﬂux. (4th March 2018) - Wang, Gang; Manni, S.; Lin, Qisheng; McVey, Patrick; Houk, Robert S.; Wu, Liming; Bud'ko, Sergey L.; Canﬁeld, Paul C.
ABSTRACT: Nitridoferrates containing monovalent iron ions are a class of materials of recent interest as potentially novel magnetic materials. Aiming at the exploration of nitridoferrates of calcium, we report the single crystal growth from Ca ﬂux and crystal structure of the first member ( n = 2) of a series of inverse Ruddlesden-Popper nitrides with a general formula of A n −1 A'2 B n X3 n +1, where A = Li/Fe, A' = Te, B = N, and X = Ca. Single crystal X-ray diffraction analyses indicate the crystal with a composition of Ca7 (Li0.32(1) Fe0.68(1) )Te2 N2 and the tetragonal space group I 4/mmm ( a = 4.7884(1) Å, c = 25.3723(4) Å, Z = 2). The structure features alternately stacking NaCl-type A'X slabs and the perovskite-type ABX3 slabs along the c axis. The Li/Fe atoms are located in cuboctahedral cavities surrounded by eight Ca6 N octahedra in the ABX3 slab. This work demonstrates the viability of the Ca-rich ﬂux as a suitable solvent for the exploration of new complex nitrides with interesting crystal structure and properties.